Conceptual Metapher in the Framework of the Specialized Language Lessons at German Studies in Lodz on the Example of the German Stock Market Reports - Grzeszczakowska-Pawlikowska, Beata; Stawikowska-Marcinkowska, Agnieszka (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
With the development of corpus linguistics, the need for natural metaphor analysis based on economic data has become more pronounced in recent years. In line with this trend the following text introduces the concept of a cognitive metaphor. It is based on examples from a number of German online stock newspapers, and addresses the issue of transparency of stock exchange markets in German economic discourse. The text shows how to easily transfer this knowledge to students of German studies. The most common metaphors were approximated on the basis of conducted research. Then, they were grouped in terms of semantics. The results of the study show that the conceptualization of stock market processes is not familiar to a non-expert. They are connected with common knowledge of the world and shared human experience as well as have become an integral part of the human conceptual system.